Mechanical Behavior of Hybrid Connectors for Rapid-Assembling Steel-Concrete Composite Beams - Lu, Senqiang; Zhao, Wei; Han, Puge; Hang, Zhenyuan (Salehan Institute of Higher Education, 2019)
In order to achieve a kind of shear connector suitable for rapid-assembling steel-concrete composite beams, a new type of hybrid shear connectors is proposed, in which the concrete slab with prefabricated circular holes and the steel beam with welded studs are installed and positioned, and then epoxy mortar is filled in the prefabricated hole to fix the studs. To study the mechanical behavior of these hybrid connectors, test on 18 push-out specimens with different prefabricated circular holes are carried out. ABAQUS finite element software is adopted to verify the relationship between the numerical simulation and experiment, influences of the epoxy mortar strength and prefabricated circular holes diameter are studied. The results show that filling epoxy mortar in the prefabricated hole is beneficial to improve the stiffness and bearing capacity of the specimen; the change of epoxy mortar strength has a certain impact on the bearing capacity and stiffness of the hybrid connector; In the case of the same strength of the filling material, the size of the prefabricated circular holes diameter directly affects the stiffness and bearing capacity of the shear stud. The shear capacity equations proposed by considering the epoxy mortar strength and prefabricated holes diameter, and it has a wide applicability.